Imunski mehanizmi proti bakterijam, virusom in zajedalcem - Ihan, Alojz (Medicinski razgledi, 1996)
Immunity consist of several mechanisms evolved to protect host organisms against infectious deseases. Microorganisms use different strategies to elict immune responses of the host. The immune system must be able to combat all invading pathogens and their virulence factors. The observed differences in the effectiveness of immune response to various infectious diseases reflect differences between individual infecting pathogens. Immune mechanisms protecting against intracellular bacteria differ from those protecting againstextrecelular bacteria. Specific protective mechanisms are involved in immunity against parasite and viral infections.
Keywords: imunski sistem; okužbe